Some factors influencing the amount of fines for forest offenses / Rusli Mohd and Nik Suryana Nik Mat - Mohd, Rusli; Nik Mat, Nik Suryana (2004)
Under the current forest law, the courts can sentence those found guilty committing forest offenses either with fines or imprison or both. However, most offenders opted to settle their cases outside the courts by paying compounds. In addition to compound, the offenders wil1 be also asked to pay compensations, particularly when it involves illegal cutting and removal of timber. The amount of compensations should be related to the volume of timber illegally cut or removed. The State Forestry Officer (SFO) has the final decision on the amount of compounds and compensations. This study investigates the effects of logs price, volume of illegal timber and the role of the SFO on the amount of penalties (compounds and compensations) for forest offenses. Data for the Forest District concerned covering the period 1983 to 2001 were analysed in the study. A linear regression model was developed to determine the effects of logs price and volume of timber on penalties while the ANAVO was run to determine the influence of the SFO. The results show that the price of logs and volume of timber significantly explain the variations in amount of penalties (F = 14.94, P = 0.00) while the SFO has a significant influence on the amount of compensations and compounds (p = 0.0 19). The implications of these findings are briefly discussed.